The Effect of LDR, Capital Structure, Operational Cost of Operational Income and NPL on ROA at the Banking Companies Listed in IDX in 2014-2018 Period - Angelia Angelia; Nagian Toni (Politeknik Negeri Bali, 2020)
In creating and maintaining sound banking, it is necessary for banking institutions to get effective guidance and supervision from the government, especially Bank Indonesia. The purpose of this study was to determine and analyze the influence of Loan to Deposit Ratio, Capital Structure, Operational Costs Operating Income and Non Performing Loans on Return on Assets in Banking Companies listed on the Indonesia Stock Exchange Period 2014-2018 This study used a quantitative research approach. This type of research is explanatory research. The population in this study were 45 banking companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sample of this research is 105 financial reports from 21 banking companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The results of the study are conclusions are the Loan to Deposit Ratio, Capital Structure, Operational Costs Operating Income, and Non Performing Loans simultaneously have a positive and significant effect on Return on Assets in registered banking companies on the Indonesia Stock Exchange in 2014-2018. Loan to Deposit Ratio and capital structure partially do not affect the Return on Assets of Banking Companies listed on the Indonesia Stock Exchange in 2014-2018. Operational Costs Operating Income and Non Performing Loans partially negatively affect the Return on Assets